One-Pot Synthesis of Alkyl Styryl Sulfides Free from Transition Metal/Ligand Catalyst and Thiols - Heredia, Adrián Alberto (2012)
A new protocol for the one-pot synthesis of styryl alkyl sulfides was developed. This methodology involves the in situ generation of thiolate anions by nucleophilic substitution between potassium thioacetate and alkyl halides followed by fragmentation. Further reactions of these thiolate anions with substituted (E,Z)-β-styryl halides gave the corresponding sulfides with retention of stereochemistry in good to excellent yields. This procedure does not require a metal catalyst, it proceeds under mild conditions and in short times, and it is free from malodorous and air-sensitive alkyl thiols.